The martial rights and duties (Rights and duties of a woman and a man) (Journal of the College of Education for Women, 2019)
This research addresses the relevance of men and women and the consequent provisionssuch as dowry and alimony ... Of the like, marriage is to organize links masculinity andfemininity any sexual meeting between men and women a special system that must beproduces reproduction him and alone, which gets its reproduction in human kind, and has nofamily and on the basis of private life is being organized.The importance of the topic see Islam has urged marriage and forbade celibacy, and ensurethat the Lord of Glory Almighty married subsidy nor the origin of the differences betweenmen and women in money or workmanship or blue-chip Every Muslim inept any Muslim andevery Muslim efficient for any Muslim.The importance of research goes back to the ignorance of women our age and even menalso rights marital any ignorance of women, because they must of rights and the consequences for them of the duties so that one of them get married and give birth to and raise and live along life with her husband and die is ignorant of the most basic rights of a spouse or ownrights or the rights of their common , and this is the same what happens to a man, too.It is a reality we live andTouchin society now is the multitude of problems and conflictsthat occur between spouses Here are the courts fill the issues of Personal Status, which lead tothe disintegration of Alosroziaa for boys and all that stems from ignorance of the peopleverdicts legitimacy and lack of proper understanding of the relationship between men andwomen, which can only be done by marriage, according to legal costs it needs in his life is anindividual duty for every Muslim because he commanded that does its work in accordancewith the provisions legislate.And the importance of conjugal rights and their impact on family formation and rearingchildren see that Islam may care about this marital relationship and singled out its provisionsand processors to disturb the elite of this link, and made interest that bind husband his wife isnoted by legislate not mind because Hassan is classed legislate and uglywhatdistortionlegislate and corrupting and interest to be determined legislate.If aware of the husband and wife what is and what Accordingly, the king of the key topeace of mind and tranquility of his life, and those rights governing marital life, andemphasizes the good treatment between spouses, and improves each and every one of them tobe given before it takes, and fulfills the rights of partner choice, voluntarily without force, andon the other to This compares charity in truth better than him, Wesera to fulfill the rights ofhis partner full of spin.